Proceso de atención de enfermería en paciente neonato de 8 días con sepsis neonatal. - Tasgacho Suarez, Cindy Katherine (2021)
Neonatal sepsis is a major cause of infant death, especially in developing countries. In Ecuador, it is classified as the third cause of infant, early diagnosis is of the utmost importance to establish proper treatment and prevent future risk factors therefore the present case study deals with a pediatric patient 8 days old. The early term newborn with Capurro assessment of 37 weeks with weight of 2760 grams born in the General Hospital IESS Quevedo, male newborn born by cesarean section in this health home by a mother with a history of previous caesarean section, newborn is in clinical care, in non-invasive ventilation nasal CPAP mode with moderate subcostal retractions, stays in non-invasive ventilation nasal CPAP mode with fi02 45% maintaining satO2 greater than 95% with moderate subcostal retractions, male newborn born by cesarean section per previous concesarean mother. Cases that have been recorded with infections during pregnancy, in order for neonatal sepsis to be present, the neonate must pass from 24 to 48 hours of life; It can also be observed that in a percentage of 10 to 15% of newborn patients are febrile this indicator is a clear sign of infection. Laboratory results showed leukocytosis19.73, neutrophils 5.94, lymphocytes 11.46, monocytes 2.31, neutrophils 30.1%, lymphocytes 58.1, Eosinophils 0%, Monocytes 11.7%, Basophils 0.1%, Erythrocytes 3.99, Hemoglobin 14.4, Hematocrit 43.2, Vol. corpuscular medium 108.2, HGB. Corpuscular mean 34.3, Conc. HGB. Corpuscular mean 31.7, Rdw-cv 16.3, Edw-sd 66.6, Platelets 354, V. platelet medium 8.5, Urea 14, Creatinine 0.3. Blood typing: positive ARh.